Transformation of the Structure of Self-Attitude in Early, Middle and Later Adulthood (on the Example of the Ukrainian Sample) - Kostytsky, Mychailo V.; Kushakova-Kostytska, Nataliia V.; Glavinska, Olena D.; Kit, Vilena O.; Leonova, Inna M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The study intends to trace the dynamics of self-esteem and changes in the structure of self-attitude at different stages of adult life, as well as identify signs of experiencing age-related crises. Self-attitude is considered a multidimensional formation, with its individual components, have different subjective significance in different periods of life. A cross-section was carried out in 507 subjects aged 25-65 years was carried out. Rosenberg Self-Esteem Scale and Self-Attitude Study Methodology by Pantileev were used. Normative data for RSES obtained on a sample of adult Ukrainians (N=488) are presented for the first time. The average interval was 22.70±5.43 (with a measuring scale of 0 to 30 points), but the reference point for low self-esteem is different for men and women. Comparison of average results in groups belonging to periods of early, middle, and later adulthood showed that the attitude towards oneself with age becomes more emotionally expressive, concerning both positive and negative components. The indicators of self-blame and inner closedness grow along with the growth of the positive self-attitude (self-confidence, self-management, self-acceptance). The heterogeneous age dynamics of components of self-attitude, pronounced peaks, and dips in different periods are shown. Based on the clustering of empirical data, we described seven types of self-attitude in adulthood: illusory, confident, accepting, crisis, externally oriented, persistently negative, and inexpressive. Markers of experiencing crisis life periods are the ambivalence of self-attitude – the simultaneous manifestation of positive and negative components, which is regarded as a sign of instability. The obtained results demonstrate that there are potential opportunities for personal growth among cases of low self-esteem.